Analisis Conceptual Cost Estimation (CCE) untuk Pembangunan Gedung Kuliah Bersama Tambahan (GKB 3) - Kevin Abdullah Alrasyid; Dian Ariestadi (Jurnal Indonesia Sosial Teknologi, 2025)
Cost estimation plays a crucial role in ensuring the feasibility and success of construction projects. However, producing accurate estimates, particularly in the early conceptual stages, remains a challenge due to limited information. This study addresses the issue by analyzing the cost estimation process for the construction of the Joint Lecture Building (GKB 3) at State University of Malang. The objective of this study is to provide an accurate and systematic cost estimation to support the construction planning of GKB 3. The study employs a conceptual cost estimation (CCE) method. Data were obtained from field surveys (primary data) and relevant regulatory standards, technical documents, and unit prices (secondary data). Key inclusion criteria include projects categorized under multi-story educational buildings. Analytical descriptive methods were used to process the data. The results indicate that the total building area for GKB 3, spanning nine floors, is 29,932 m², with an estimated cost of IDR 865,037,221,000. This amount includes standard costs, non-standard costs, and Value Added Tax (VAT). Standard costs were calculated using the building's area, multiplying factors, and unit price standards. Non-standard costs, such as installations for air conditioning, elevators, and fire protection systems, were estimated based on regulatory guidelines and their respective percentages of standard costs. In conclusion, the study highlights the importance of employing systematic and regulation-based estimation methods to achieve accurate cost calculations. This approach ensures efficient resource allocation and supports strategic planning for the construction of educational infrastructure.